Arbuscular Mycorrhizal Fungi Improve Tolerance of the Medicinal Plant Eclipta prostrata (L.) and Induce Major Changes in Polyphenol Profiles Under Salt Stresses - Duc, Nguyen Hong; Vo, Au Trung; Haddidi, Imane; Daood, Hussein; Posta, Katalin (Frontiers in Plant Science, 2021)
Eclipta prostrata (L.) is an important and well-known medicinal plant due to its valuable bioactive compounds. Microorganisms, including arbuscular mycorrhizal fungi (AMF), and salinity could directly impact plant metabolome, thus influencing their secondary metabolites and the efficacy of herbal medicine. In this study, the role of different single AMF species (Funneliformis mosseae, Septoglomus deserticola, Acaulospora lacunosa) and a mixture of six AMF species in plant growth and physio-biochemical characteristics of E. prostrata under non-saline conditions was investigated. Next, the most suitable AM treatment was chosen to examine the impact of AMF on physio-biochemical features and polyphenol profiles of E. prostrata under saline conditions (100 and 200 mM NaCl). The findings indicated that AMF mixture application resulted in more effective promotion on the aboveground part of non-saline plants than single AMF species. AM mixture application improved growth and salt tolerance of E. prostrata through increasing the activity of catalase, peroxidase (at 4 weeks), proline, and total phenolic content (at 8 weeks). Such benefits were not observed under high salinity, except for a higher total phenolic concentration in mycorrhizal plants at 8 weeks. Through high-performance liquid chromatography, 14 individual phenolic compounds were analyzed, with wedelolactone and/or 4,5-dicaffeoylquinic acid abundant in all treatments. Salinity and mycorrhizal inoculation sharply altered the polyphenol profiles of E. prostrata. Moderate salinity boosted phenolic compound production in non-AM plants at 4 weeks, while at 8 weeks, the decline in the content of phenolic compounds occurred in uncolonized plants subjected to both saline conditions. Mycorrhization augmented polyphenol concentration and yield under non-saline and saline conditions, depending on the growth stages and salt stress severity. Plant age influenced polyphenol profiles with usually a higher content of phenolic compounds in older plants and changed the production of individual polyphenols of both non-AM and AM plants under non-stress and salt stress conditions. A better understanding of factors (involving mycorrhiza and salinity) affecting the phenolic compounds of E. prostrata facilitates the optimization of individual polyphenol production in this medicinal plant.